Evaluation of the effect of dentin treatment with CO2 laser and air abrasion on the microleakage of composite restoration. (Mustansiria Dental Journal, 2019)
Abstract Objectives: The purpose of this study was to compare the microleakage of composite restoration at dentin following treatment with CO2 laser, Air Abrasion, Combination between them and acid.Methods: 100extracted maxillary premolars (caries free), stored in distilled water, were used. Flat occlusal dentin surfaces were grounded wet on 600- grit silicon carbide paper. Cube cavities were prepared at the center of the occlusal surfaces. Teeth were then distributed randomly in to five groups, 20 teeth each:Group A: Teeth were treated by CO2 laser (with 10.6 µm wave length, 6 W, 0.2 s and 2 H z).Group B: Teeth were treated by air abrasion (using aluminum oxide particles size 50 micrometers and air flow handy device at 1.2 cm distance with 15 seconds perpendicular application, air pressure was 2.75 bar and water pressure was 0.6 bar).Group C: Teeth were treated by 37% phosphoric acid for 20 seconds.Group D: Teeth were treated by CO2 laser and 37% phosphoric acid.Group E: Teeth treated by air abrasion and 37% phosphoric acid.All the cavities were restored with the same bonding and composite materials and stored in distilled water in an incubator at 37o C. Half of each group were stored for 1 day and themocycled between 5-55oC, (10 cycles) while the other half were stored for 14days and thermocycled between 5-55oC, (140 cycles). Then teeth were immersed in the 2% methylene blue dye and the extent of the dye penetration was recorded according to an ordinal scale. Data were analyzed using non- parametric statistical tests (Chi-square and Mann-Whitney)  Results: Microleakage in acid etched cavities was significantly higher than that achieved after laser treatment or air abrasion either isolated or followed by acid etch.Conclusion:The use of CO2 laser, air abrasion to condition dentin significantly reduced the microleakage of composite restoration, while there was no significant decrease in microleakage when using acid etching on dentin following CO2 laser or air abrasion. There was statistically increase in microleakage with in times when using acid to condition dentin.